Self-Reported Practices in Opioid Management of Chronic Noncancer Pain: A Survey of Canadian Family Physicians - Michael JM Allen; Mark M Asbridge; Peter C MacDougall; Andrea D Furlan; Oleg Tugalev (Pain Research and Management)
BACKGROUND: In May 2010, a new Canadian guideline on prescribing opioids for chronic noncancer pain (CNCP) was released. To assess changes in family physicians’ (FPs) prescribing of opioids following the release of the guideline, it is necessary to know their practices before the guideline was widely disseminated.